1996
DOI: 10.3171/jns.1996.84.3.0400
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results in direct carotid-cavernous fistulas after treatment with detachable balloons

Abstract: Transarterial embolization of direct carotid-cavernous fistulas (CCFs) using detachable balloons is the best initial option for occlusion of the fistula and preservation of the internal carotid artery. However, the long-term safety and efficacy of this treatment is unknown. The authors reviewed the long-term outcome of 87 patients with 88 direct CCFs occluded by detachable balloons. Clinical follow up was obtained in 48 (83%) of 58 patients treated with latex balloons (mean follow-up period 10 years, range 5.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 13 publications
0
69
0
4
Order By: Relevance
“…Higashida et al [15] reported preservation of the parent artery in 88% of patients with TCCFs treated by using detachable balloons; other authors have described a need for parent artery occlusion in as many as 20% of cases [16,17].…”
Section: Review Of Endovascular Management Of Traumatic Carotid-cavermentioning
confidence: 99%
“…Higashida et al [15] reported preservation of the parent artery in 88% of patients with TCCFs treated by using detachable balloons; other authors have described a need for parent artery occlusion in as many as 20% of cases [16,17].…”
Section: Review Of Endovascular Management Of Traumatic Carotid-cavermentioning
confidence: 99%
“…Detachable balloons quickly became the method of choice to treat CCF following introduction in the 1970s, [1][2][3]12,19) with preserved patency of the parent ICA in 75-88% of cases. 2,4,6,[10][11][12][13]16) However, detachable balloons cannot be used if preservation of the parent artery is essential, leading to a search for other ways to treat CCF, such as detachable coils and cyanoacrylates. 4,8,11) Direct CCFs have been successfully occluded with coil embolization via either the transarterial or transvenous approach.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,6,[10][11][12][13]16) However, detachable balloons cannot be used if preservation of the parent artery is essential, leading to a search for other ways to treat CCF, such as detachable coils and cyanoacrylates. 4,8,11) Direct CCFs have been successfully occluded with coil embolization via either the transarterial or transvenous approach. 8,9,14,15,21) Guglielmi detachable coil (GDC) is effective for direct CCFs with small fistulas and/or small cavernous sinuses, because a limited number of GDCs will be required to achieve angiographic cure.…”
Section: Introductionmentioning
confidence: 99%
“…La mayoría de las FCC directas pueden cerrarse mediante tratamiento endovascular, generalmente por vía arterial mediante coils o balones 8,17 , aunque también se han obtenido buenos resultados por vía venosa 13 . El tratamiento de las FCC indirectas o durales es más complicado, siendo la vía venosa de elección para la mayoría de los autores 1,7,12,18,21,26 .…”
Section: Introductionunclassified